Wine tourism and hedonic experience: A motivation-based experiential view. (October 2019) - Bruwer, Johan; Rueger-Muck, Edith
This study adopts the experiential and more specifically a hedonic view of tourism consumption to examine the nature of wine tourist motivations in a wine region destination. It also determines the effect of destination factors such as the perceived characteristics of the wine region, previous visitation, buying behavior, and age generational cohorts. Information was obtained from a random sample of 513 visitors to the Barossa Valley Region in Australia. The most important destination characteristic is the regional landscape's scenic beauty. The strong impact of the landscape confirms an experiential research approach can yield valuable insights and that a memorable wine tourism experience does not only evolve inside a winery's cellar door. The wine tourism engagement decision is generally impulsive, and motivations guiding visitors' behavior predominantly hedonic in nature. Wine tourists are a highly attractive group of consumers who are well-educated, affluent, and eager to buy when they experience "pleasure."